Professional reflection as a condition of formation of innovational activity of the future teacher - Chernuha, N.M.; Muromets, V.H. (Pedagogy of Higher and Secondary Education, 2007)
In the article is examined and is determined psychological -pedagogical aspect of forming of professional reflection in the conditions of innovative activity offuture teachers.